Performance of TiO2/Ag/CA for efficient adsorption of methylene blue - Devagi, Kanakaraju; Feniellia Diwvya, Kutiang; Sheikh Mohammad Fareth, Abdul Hadi; Ying Chin, Lim (Springer, 2022)
The incorporation of additives and inclusion of metal dopants on titanium dioxide (TiO2) could improve its inherent limitations and result in enhanced photocatalytic efficiency. In this work, the performance of TiO2/ Ag with the use of cellulose acetate (CA) was investigated for the degradation of a model dye pollutant under different operational settings. The surface morphology, elemental composition, crystallinity, and band gap of TiO2/ Ag/CA composite were verified by scanning electron microscopy, energy-dispersive X-ray, X-ray diffraction, and UV–Vis diffuse reflectance spectroscopy, respectively. An increase in CA concentration from 1 to 2 wt% led to the high removal of methylene blue (MB). The highest removal of MB (90.90%) was obtained by TiO2/Ag/CA under the conditions of 4 g/L catalyst loading, 5 ppm MB concentration, and at unadjusted pH (7.8). The recyclability study showed that the removal efficiency of the retrieved photocatalyst remains as much as ~ 78% after 3 cycles, demonstrating its sustainability in water treatment. The remarkable adsorption effect shown by CA as an additive greatly enhanced the removal of MB by the TiO2/Ag photocatalyst under UV irradiation and dark condition. The TiO2/Ag/CA composite, which has dual roles in adsorption and photocatalysis, could be employed as a pollutionremoval agent in water.